Firewood management practice by hoteliers and non-hoteliers in Langtang valley, Nepal Himalayas - Chapagain, Prem Sagar (Geographical Journal of Nepal, 2017)
Langtang Region is the third largest trekking destination in Nepal. The annual tourist flow was about 8000 by 2000. However, after 2000, the number of tourists were increased to about 15000 annually. Out of it, one third tourists visit to the Langtang Valley. With increasing number of tourists, the number of hotels and lodges are also rapidly increased there. Firewood has been the major source of energy for both hoteliers and non-hoteliers for a long time and its demand has been abruptly increased with increasing number of hotels and lodges. Both hoteliers and non-hoteliers collect firewood from nearby forest and also transport from the valley bottom to Langtang village and Kyanjing. However, there are major differences in collection places, and collection strategy especially in terms of distance, preference of tree species, purpose, and relation to nature. The Geographical Journal of Nepal Vol. 10: 55-72, 2017